Defining OER-Enabled Pedagogy - Wiley, David; Hilton III, John Levi (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2018)
The term “open pedagogy” has been used in a variety of different ways over the past several decades. In recent years, its use has also become associated with Open Educational Resources (OER). The wide range of competing definitions of open pedagogy, together with its semantic overlap with another underspecified term, open educational practices, makes it difficult to conduct research on the topic of open pedagogy. In making this claim we do not mean to cast doubt on the potential effectiveness of the many pedagogical approaches labeled open. In this article, rather than attempting to argue for a canonical definition of open pedagogy, we propose a new term, “OER-enabled pedagogy,” defined as the set of teaching and learning practices that are only possible or practical in the context of the 5R permissions that are characteristic of OER. We propose criteria used to evaluate whether a form of teaching constitutes OER-enabled pedagogy and analyze several examples of OER-enabled pedagogy with these criteria.